Bokabularyong traylinggwal Bikol, Naga-Filipino-English. - Philippines. Komisyon sa Wikang Filipino (San Miguel, Maynila Komisyon sa Wikang Filipino, 2003)
Philippine dictionary of Bikol, Tagalog, and English languages.
Bikol, Tagalog, and English.
Keywords: English language--Dictionaries--Bicol (Naga).